DAYA TERIMA SNACK BAR KARAPOSA - Retno Sri Lestari; thresia dewi kartini berek; chaerunnimah chaerunnimah; rizki ayu ningtyas (Jurusan Gizi Poltekkes Kemenkes Makassar, 2022)
Background, These food products have sufficient nutritional content to meet the needs during activities or when a person does not have enough time to eat. One practical food is a snack bar. Banana dumplings or banana sale can be eaten directly or processed into other food products, such as snack bars. Snack bar Karaposa is a snack bar based on local food, namely red beans and banana dampo.The aim, of the study was to assess the acceptability of the Karaposa snack bar.Design, pre-experimental research with post-test group design. This study provides treatment with the addition of banana dampo with concentrations of 0%, 10%, and 20% of the weight of the main ingredient on the snack bar.Results, of the study based on the average acceptability test score showed that the F1 snack bar Karaposa formula was the most preferred by the panelists from the aspect of color, aroma, texture and taste. Although Friedman test results showed that there was an effect of adding dampo banana to the color and aroma of the Karaposa snack bar, it was not significantly different between formulas F0, F1 and F2.Conclusion, The F1 formula for the Karaposa snack bar with the addition of 10% dampo banana was the most preferred by the panelists.Produk makanan tersebut memiliki kandungan gizi yang cukup untuk memenuhi kebutuhan saat beraktivitas atau ketika seseorang tidak mempunyai waktu yang cukup untuk makan. Salah satu makanan praktis adalah snack bar. Dampo pisang atau pisang sale dapat dimakan langsung atau diolah menjadi produk makanan lainnya, seperti snack bar. Snack bar Karaposa merupakan snack bar berbasis pangan lokal, yaitu kacang merah dan dampo pisang. Tujuan penelitian untuk menilai daya terima snack bar Karaposa. Penelitian pra eksperimental dengan desain post test grup design. Penelitian ini memberikan perlakuan penambahan dampo pisang dengan konsentrasi 0%, 10%, dan 20% dari berat bahan utama pada snack bar. Hasil penelitian berdasarkan rata-rata skor uji daya terima menunjukkan formula F1 snack bar Karaposa yang paling disukai panelis dari aspek warna, aroma, tekstur dan rasa. Meskipun hasil uji Friedman menunjukkan ada pengaruh penambahan dampo pisang terhadap warna dan aroma snack bar Karaposa, tetapi tidak berbeda nyata diantara formula F0, F1 dan F2. Kesimpulannya formula F1 snack bar Karaposa dengan penambahan dampo pisang 10% yang paling disukai panelis.